Topological Model for Boroaluminosilicate Glass Hardness - Smedskjaer, Morten M. (Frontiers in Materials, 2014)
For various advanced glass applications, it is important to understand the composition dependence of indentation hardness. Boroaluminosilicate glasses form the basis of many industrial products and they exhibit complex structural behavior due to the mixed network-former effect. Based on available structural NMR data and a previously proposed approach, we here establish a temperature-dependent constraint model of indentation hardness of sodium boroaluminosilicate glasses. The model correctly predicts the trends of hardness with varying Si/Al and Na/B ratios, including local minima and maxima at intermediate compositions. This topological approach is thus proving to be a valuable tool for exploring and designing new boroaluminosilicate glass compositions with tailored hardness.